The Advantages of Corporate Social Responsibility (CSR) Activities for Micro, Small, and Medium Enterprises (MSMEs) in Bangkalan Regency - Ubadah Muqtafibillah; Nurita Andriani; Muh. Syarif (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
Corporate Social Responsibility (CSR) represents a form of corporate social commitment that not only benefits the surrounding community but also provides significant advantages for Micro, Small, and Medium Enterprises (MSMEs). This article explores the strategic value and practical implications of CSR activities targeted at MSMEs in Bangkalan Regency. By employing a qualitative descriptive approach, the study aims to identify how CSR programs contribute to improving product quality, expanding market access, and strengthening the overall competitiveness of local MSMEs. In addition, the research highlights the role of CSR in fostering innovation, enhancing managerial capabilities, and creating sustainable business practices among small business owners. The findings reveal that the effectiveness of CSR initiatives largely depends on active collaboration and mutual trust between corporations, MSMEs, and local government bodies. A well-coordinated CSR program has the potential to drive inclusive economic development and reduce regional disparities. However, several challenges still hinder its implementation, including limited resources, inconsistent program monitoring, and lack of long-term commitment from stakeholders. This article concludes by offering recommendations to enhance the impact of CSR initiatives, such as fostering public-private partnerships, increasing transparency, and aligning CSR objectives with local development goals. These efforts are essential to ensure that CSR becomes a sustainable tool for empowering MSMEs and boosting regional economic resilience.